The pain of not learning: between helplessness, isolation, indifference, and possibility (Praxis Educativa, 2026)
Abstract:This article addresses the emotional and social pain caused by non-learning in educational contexts, analyzing its ethical, affective, and pedagogical implications. Through a critical reflection, it examines the causes and consequences of this issue, including isolation, frustration, and the loss of the desire to learn. The text highlights the importance of legitimate pedagogical authority and reflective and transformative educational practices that foster emotional support and meaningful learning. Furthermore, it emphasizes the role of the educational community as a collective space of inclusion and support, where the interaction between academic, social, and emotional aspects allows the transformation of suffering into growth. Finally, it stresses the need for a pedagogy based on recognition, dialogue, and hope, capable of signifying the pain of non-learning and promoting comprehensive and humanizing educational trajectories.
Keywords: non-learning; pedagogical authority; support; inclusion; critical reflection